Gap junctions in C. elegans - Simonsen, Karina; Moerman, Donald; Naus, Christian C. (Frontiers in Physiology, 2014)
As in other multicellular organisms, the nematode Caenorhabditis elegans uses gap junctions to provide direct cell-to-cell contact. The nematode gap junctions are formed by innexins (invertebrate analogs of the connexins); a family of proteins that surprisingly share no primary sequence homology, but do share structural and functional similarity with connexins. The model organism C. elegans contains 25 innexin genes and innexins are found in virtually all cell types and tissues. Additionally, many innexins have dynamic expression patterns during development, and several innexins are essential genes in the nematode. C. elegans is a popular invertebrate model due to several features including a simple anatomy, a complete cell lineage, sequenced genome and an array of genetic resources. Thus the worm has potential to offer valuable insights into the various functions of gap junction mediated intercellular communication.